<< Chapter < Page Chapter >> Page >

Write each of the following products with a single base. Do not simplify further.

  1. k 6 k 9
  2. ( 2 y ) 4 ( 2 y )
  3. t 3 t 6 t 5
  1. k 15
  2. ( 2 y ) 5
  3. t 14
Got questions? Get instant answers now!

Using the quotient rule of exponents

The quotient rule of exponents allows us to simplify an expression that divides two numbers with the same base but different exponents. In a similar way to the product rule, we can simplify an expression such as y m y n , where m > n . Consider the example y 9 y 5 . Perform the division by canceling common factors.

y 9 y 5 = y y y y y y y y y y y y y y = y y y y y y y y y y y y y y = y y y y 1 = y 4

Notice that the exponent of the quotient is the difference between the exponents of the divisor and dividend.

a m a n = a m n

In other words, when dividing exponential expressions with the same base, we write the result with the common base and subtract the exponents.

y 9 y 5 = y 9 5 = y 4

For the time being, we must be aware of the condition m > n . Otherwise, the difference m n could be zero or negative. Those possibilities will be explored shortly. Also, instead of qualifying variables as nonzero each time, we will simplify matters and assume from here on that all variables represent nonzero real numbers.

The quotient rule of exponents

For any real number a and natural numbers m and n , such that m > n , the quotient rule of exponents states that

a m a n = a m n

Using the quotient rule

Write each of the following products with a single base. Do not simplify further.

  1. ( −2 ) 14 ( −2 ) 9
  2. t 23 t 15
  3. ( z 2 ) 5 z 2

Use the quotient rule to simplify each expression.

  1. ( −2 ) 14 ( −2 ) 9 = ( −2 ) 14 9 = ( −2 ) 5
  2. t 23 t 15 = t 23 15 = t 8
  3. ( z 2 ) 5 z 2 = ( z 2 ) 5 1 = ( z 2 ) 4
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Write each of the following products with a single base. Do not simplify further.

  1. s 75 s 68
  2. ( −3 ) 6 −3
  3. ( e f 2 ) 5 ( e f 2 ) 3
  1. s 7
  2. ( −3 ) 5
  3. ( e f 2 ) 2
Got questions? Get instant answers now!

Using the power rule of exponents

Suppose an exponential expression is raised to some power. Can we simplify the result? Yes. To do this, we use the power rule of exponents . Consider the expression ( x 2 ) 3 . The expression inside the parentheses is multiplied twice because it has an exponent of 2. Then the result is multiplied three times because the entire expression has an exponent of 3.

( x 2 ) 3 = ( x 2 ) ( x 2 ) ( x 2 ) 3  factors = ( x x 2  factors ) ( x x 2  factors ) ( x x 2  factors ) 3  factors = x x x x x x = x 6

The exponent of the answer is the product of the exponents: ( x 2 ) 3 = x 2 3 = x 6 . In other words, when raising an exponential expression to a power, we write the result with the common base and the product of the exponents.

( a m ) n = a m n

Be careful to distinguish between uses of the product rule and the power rule. When using the product rule, different terms with the same bases are raised to exponents. In this case, you add the exponents. When using the power rule, a term in exponential notation is raised to a power. In this case, you multiply the exponents.

Product Rule  Power Rule 5 3 5 4 = 5 3 + 4 = 5 7 but   ( 5 3 ) 4 = 5 3 4 = 5 12 x 5 x 2 = x 5 + 2 = x 7 but ( x 5 ) 2 = x 5 2 = x 10 ( 3 a ) 7 ( 3 a ) 10 = ( 3 a ) 7 + 10 = ( 3 a ) 17 but ( ( 3 a ) 7 ) 10 = ( 3 a ) 7 10 = ( 3 a ) 70

The power rule of exponents

For any real number a and positive integers m and n , the power rule of exponents states that

( a m ) n = a m n

Using the power rule

Write each of the following products with a single base. Do not simplify further.

  1. ( x 2 ) 7
  2. ( ( 2 t ) 5 ) 3
  3. ( ( −3 ) 5 ) 11

Use the power rule to simplify each expression.

  1. ( x 2 ) 7 = x 2 7 = x 14
  2. ( ( 2 t ) 5 ) 3 = ( 2 t ) 5 3 = ( 2 t ) 15
  3. ( ( −3 ) 5 ) 11 = ( −3 ) 5 11 = ( −3 ) 55
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

root under 3-root under 2 by 5 y square
Himanshu Reply
The sum of the first n terms of a certain series is 2^n-1, Show that , this series is Geometric and Find the formula of the n^th
amani Reply
cosA\1+sinA=secA-tanA
Aasik Reply
why two x + seven is equal to nineteen.
Kingsley Reply
The numbers cannot be combined with the x
Othman
2x + 7 =19
humberto
2x +7=19. 2x=19 - 7 2x=12 x=6
Yvonne
because x is 6
SAIDI
what is the best practice that will address the issue on this topic? anyone who can help me. i'm working on my action research.
Melanie Reply
simplify each radical by removing as many factors as possible (a) √75
Jason Reply
how is infinity bidder from undefined?
Karl Reply
what is the value of x in 4x-2+3
Vishal Reply
give the complete question
Shanky
4x=3-2 4x=1 x=1+4 x=5 5x
Olaiya
hi can you give another equation I'd like to solve it
Daniel
what is the value of x in 4x-2+3
Olaiya
if 4x-2+3 = 0 then 4x = 2-3 4x = -1 x = -(1÷4) is the answer.
Jacob
4x-2+3 4x=-3+2 4×=-1 4×/4=-1/4
LUTHO
then x=-1/4
LUTHO
4x-2+3 4x=-3+2 4x=-1 4x÷4=-1÷4 x=-1÷4
LUTHO
A research student is working with a culture of bacteria that doubles in size every twenty minutes. The initial population count was  1350  bacteria. Rounding to five significant digits, write an exponential equation representing this situation. To the nearest whole number, what is the population size after  3  hours?
David Reply
v=lbh calculate the volume if i.l=5cm, b=2cm ,h=3cm
Haidar Reply
Need help with math
Peya
can you help me on this topic of Geometry if l help you
litshani
( cosec Q _ cot Q ) whole spuare = 1_cosQ / 1+cosQ
Aarav Reply
A guy wire for a suspension bridge runs from the ground diagonally to the top of the closest pylon to make a triangle. We can use the Pythagorean Theorem to find the length of guy wire needed. The square of the distance between the wire on the ground and the pylon on the ground is 90,000 feet. The square of the height of the pylon is 160,000 feet. So, the length of the guy wire can be found by evaluating √(90000+160000). What is the length of the guy wire?
Maxwell Reply
the indicated sum of a sequence is known as
Arku Reply
how do I attempted a trig number as a starter
Tumwe Reply
cos 18 ____ sin 72 evaluate
Het Reply
Practice Key Terms 1

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask